Learn in your speed, with individual attention - Teachoo Maths 1-on-1 Class

Examples

Example 1

Example 2 Important

Example 3

Example 4

Example 5 Important

Example 6 Important

Example 7 Important

Example 8

Example 9 Important

Example 10

Example 11 Important

Example 12

Example 13

Example 14

Example 15

Example 16 Important

Example 17 Important

Example 18 Important

Example 19 You are here

Example 20 Important

Example 21 Important

Example 22 Important

Question 1 Deleted for CBSE Board 2024 Exams

Question 2 Deleted for CBSE Board 2024 Exams

Question 3 Deleted for CBSE Board 2024 Exams

Question 4 Deleted for CBSE Board 2024 Exams

Question 5 Important Deleted for CBSE Board 2024 Exams

Question 6 Deleted for CBSE Board 2024 Exams

Question 7 Important Deleted for CBSE Board 2024 Exams

Chapter 3 Class 11 Trigonometric Functions

Serial order wise

Last updated at May 29, 2023 by Teachoo

Example 26 Prove that cos 2x cos 𝑥/2 – cos 3x cos 9𝑥/2 = sin 5x sin 5𝑥/2 Solving L.H.S Solving cos 2x cos x/2 and cos 3x cos 9𝑥/2 separately We know that 2 cos x cos y = cos (x + y) + cos (x – y) cos x cos y = 1/2 ("cos (x + y) + cos (x – y)" ) cos 2x cos 𝒙/𝟐 Replacing x with 2x and y with 𝑥/2 = 1/2 ("cos " ("2x + " x/2)" + cos" ("2x" −x/2)) = 1/2 ("cos " ((4x + x )/2)" + cos " ((4x − x)/2)) = 1/2 ("cos " (5x/2)" + cos " (3x/2)) cos 3x cos 𝟗𝒙/𝟐 Replacing x with 3x and y with 9𝑥/2 = 1/2 ("cos" ("3x + " 9𝑥/2)" + cos " ("3x – " 9𝑥/2)) = 1/2 ("cos " ((6𝑥 + 9𝑥 )/2)" + cos " ((6𝑥 − 9𝑥)/2)) = 1/2 ("cos " (15𝑥/2)" + cos " ((−3𝑥)/2)) Now, cos 2x cos 𝑥/2 – cos 3x cos 9𝑥/2 Putting values = 1/2 ("cos " (5x/2)" + cos " (3x/2)) – 1/2 ("cos " (15𝑥/2)" + cos " ((−3𝑥)/2)) = 1/2 ("cos " (5x/2)" + cos " (3x/2)) – 1/2 ("cos " (15𝑥/2)" + cos " (3𝑥/2)) = 1/2 ("cos " (5x/2)" + cos " (3x/2)"– cos " (15𝑥/2)"– cos " (3𝑥/2)) = 1/2 ("cos " (5x/2)"– cos " (15𝑥/2)"+ cos " (3x/2)"– cos " (3𝑥/2)) = 1/2 ("cos " (5x/2)"– cos " (15𝑥/2)"+ " 0) = 1/2 ("cos " (5x/2)"– cos " (15𝑥/2)) = 1/2 ("– 2 sin " ((5𝑥/2 +15/2 𝑥)/2)". sin " ((5𝑥/2 − 15/2 𝑥)/2)) = −"sin " ((5𝑥 + 15𝑥)/(2 × 2))" . sin " ((5𝑥 − 15𝑥)/(2 × 2)) = "– sin " (20𝑥/4)" . sin " (( −10𝑥)/4) Using cos x – cos y = –2 sin (𝑥 + 𝑦)/2 sin (𝑥 − 𝑦)/2 Putting x = 5𝑥/2 , y = 15𝑥/2 = − "sin " (5𝑥)" . sin " (( −5𝑥)/2) = − "sin " (5𝑥) × −" sin " (( 5𝑥)/2) = sin (5𝑥) sin (( 5𝑥)/2) = R.H.S Hence L.H.S. = R.H.S. Hence proved (As sin(–x) = – sin x)